2014
DOI: 10.1371/journal.pone.0113945
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Anesthetics on the Renal Sympathetic Response to Anaphylactic Hypotension in Rats

Abstract: The autonomic nervous system plays an important role in rat anaphylactic hypotension. It is well known that sympathetic nerve activity and cardiovascular function are affected by anesthetics. However, the effects of different types of anesthesia on the efferent renal sympathetic nerve activity (RSNA) during anaphylactic hypotension remain unknown. Therefore, we determined the renal sympathetic responses to anaphylactic hypotension in anesthetized and conscious rats and the roles of baroreceptors in these respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 24 publications
1
29
3
Order By: Relevance
“…However, this did not occur in the current study. The sympathetic response to anaphylaxis was attenuated in anaesthetized rats, compared to conscious rats (Sun et al., ). Thus, anaesthesia might have influenced the BAT‐SNA response to anaphylactic hypotension.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…However, this did not occur in the current study. The sympathetic response to anaphylaxis was attenuated in anaesthetized rats, compared to conscious rats (Sun et al., ). Thus, anaesthesia might have influenced the BAT‐SNA response to anaphylactic hypotension.…”
Section: Discussionsupporting
confidence: 94%
“…Thus, anaphylactic hypotension may affect the medullary neural pathway containing GABA neurons in the NTS and C1 neurons in the RVLM to enhance renal and adrenal SNA. Notably, c‐fos immunoreactivity was increased in the RVLM and caudal NTS by anaphylactic hypotension in SAD rats, with renal (Sun et al., ) and adrenal sympathoexcitation. Thus, these lines of evidence suggested that anaphylaxis in the anaesthetized rats activated the medullary areas, including the caudal NTS and RVLM, independently of baroreceptors, which resulted in sympathoexcitation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations